Comparing Three Caries Prevention Products on Dentinal Hypersensitivity - A Pilot Study - Faden, Esra. (Tufts University. Tisch Library., 2020)
Thesis (M.S.)--Tufts University, 2019.; Submitted to the Dept. of Periodontology.; Advisor: Irina Dragan.; Committee: Andreas Parashis, Britta Magnusson, Gerard Kugel, and Sarah Pagni.; Keyword: Dentistry.